Innovation and the survival of new firms across British regions - Helmers, C; Rogers, M (University of Oxford, 2008)
This paper analyses the survival of the complete cohort of more than 162,000 limited companies incorporated in Britain in 2001 over the subsequent five-year period. For this purpose, we estimate firms' hazards of failure and survival functions using nonparametric and semi-parametric techniques. The paper focuses on two important policy-related issues. The first is to what extent survival rates vary across regions in Britain. A second, and related, policy issue concerns innovation. The data available allows us to look at the intellectual property (IP) activity of all British firms, including that of the 162,000 new firms in 2001. The results indicate substantial differences in survival rates across regions, and also that IP activity is associated with a higher probability of survival. These differences across regions, and the importance of IP activity, remain when we condition on a large range of regional, industry and firm-level characteristics shifting firms' hazards of failure.